2010
DOI: 10.1055/s-0030-1261922
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the German Version of the Impact of Weight on Quality of Life-Lite (IWQOL-Lite) Questionnaire

Abstract: The results of the present study suggest that the German IWQOL-Lite is a psychometrically validated instrument with which to measure weight-specific health related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 7 publications
1
29
0
1
Order By: Relevance
“…In the present study, the relationship found between the IWQOL-Lite and measures of psychopathology and self-perception supports the construct validity of the instrument. This is again consistent with previous studies, in which the IWQOL-Lite was significantly inversely correlated with other measures of psychopathology [13,15]. The analysis of the relationship between the IWQOL-Lite and self-perception items is also consistent with the findings of Masheb et al [37], who found self-esteem and body dissatisfaction to be more impaired in severely obese patients awaiting bariatric surgery.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, the relationship found between the IWQOL-Lite and measures of psychopathology and self-perception supports the construct validity of the instrument. This is again consistent with previous studies, in which the IWQOL-Lite was significantly inversely correlated with other measures of psychopathology [13,15]. The analysis of the relationship between the IWQOL-Lite and self-perception items is also consistent with the findings of Masheb et al [37], who found self-esteem and body dissatisfaction to be more impaired in severely obese patients awaiting bariatric surgery.…”
Section: Discussionsupporting
confidence: 91%
“…The IWQOL-Lite scores obtained were slightly higher than those of a sample of North American bariatric surgery patients [25]. Similarly, these Spanish patients scored slightly higher on physical function, self-esteem, and work and had higher total transformed scores, than did the severely obese patients studied in the German validation [13] of the IWQOL-Lite (A. Mueller, personal communication). By contrast, the present study found lower quality of life in the sexual life and public distress domains compared with the German data, as well as in comparison to clinical and community samples from Brazil and Portugal [12,18].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations